2016
DOI: 10.1097/bcr.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Grip and Muscle Strength Dynamometry Are Reliable and Valid in Patients With Unhealed Minor Burn Wounds

Abstract: Small burns are common and can cause disproportionate levels of disability. The ability to measure muscle impairment and consequent functional disability is a necessity during rehabilitation of patients. This study aimed to determine the reliability and validity of grip and muscle strength dynamometry in patients with unhealed, minor burn wounds. Grip and muscle strength were assessed three times on each side. Assessment occurred at presentation for the initial injury and again every other day (or every 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…The sensitivity of MSD can be interpreted from the calculated MDD's for this group. The MDD's in this group are greater during the initial testing period when compared to our previous work which assessed MDD's on the first testing session [4]. Larger MDD's indicate greater variability and suggest that comparison between muscle strength measures, particularly at different time points of the healing continuum, should be made carefully as changes in the assessed muscle strength may be attributed to changes in a number of performance factors other than an appreciable change in strength.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…The sensitivity of MSD can be interpreted from the calculated MDD's for this group. The MDD's in this group are greater during the initial testing period when compared to our previous work which assessed MDD's on the first testing session [4]. Larger MDD's indicate greater variability and suggest that comparison between muscle strength measures, particularly at different time points of the healing continuum, should be made carefully as changes in the assessed muscle strength may be attributed to changes in a number of performance factors other than an appreciable change in strength.…”
Section: Discussioncontrasting
confidence: 53%
“…5 -40% TBSA). Thus, we have demonstrated that our updated HHD testing protocol improves on the previous standard method [4] and extends the applicable TBSA range from 0 -40% TBSA, providing a reliable tool for evaluating within session muscle strength in this patient A c c e p t e d M a n u s c r i p t group. Clinically acceptable reliability was demonstrated for all assessed periods of injury acuity.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The participant will be requested to press the dynamometer with maximum force. Three trials with each hand will be carried out [19].…”
Section: Discussionmentioning
confidence: 99%